Tri Hita Karana As An Ethical And Strategic Foundation In Local Fruit Farming Enterprises In Bali - Amrita, Nyoman Dwika Ayu; Mandiyasa, I Kadek Sara; Dartawan, I Made Agus (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
This research explores the significance of Tri Hita Karana—a traditional Balinese philosophy that highlights harmony among the divine, humans, and nature—as an ethical and strategic framework in local fruit farming businesses in Bali. Using a qualitative literature study approach, this research analyzes scholarly articles to understand how the principles of parhyangan (harmony with God), pawongan (harmony with people), and palemahan (harmony with the environment) shape farmers’ ethical behaviors and strategic decision-making. The findings reveal that the incorporation of Tri Hita Karana values significantly fosters environmentally friendly ethics and socially responsible practices. Furthermore, these values guide farmers in developing adaptive, culturally rooted strategies that enhance resilience and sustainability. This study contributes to sustainability theory by demonstrating how indigenous wisdom can be integrated into modern agricultural business models. It also offers practical insights for policymakers and farmers aiming to achieve economic viability while preserving cultural and environmental integrity in Bali’s agricultural sector.